Competitiveness of Malaysian palm oil in the world market / Nurul Masniza Mohd Sobri - Mohd Sobri, Nurul Masniza (Faculty of Plantation and Agrotechnology, 2017)
Since the last decade the demand for vegetable oils has been growing strongly due to increase in global population and oils consumption. Palm oil also is one of the most important vegetable oils in the world and each year million tonnes of palm oil has been traded globally to be consumed by million people around the world. Malaysia is the second largest producer of palm oil after Indonesia and become the most important industry in growth and development of Malaysia economic. Regarding the matter, the aim of the study is to determine the production of palm oil in the world market, to identify the rate of Malaysia trade of palm oil importer and exporter in the world market and to measure the sustainability status of Malaysia palm oil industry development. In this study, the data uses were collected from FOASTAT, Index Mundi and Department of Statistic (Malaysia) from period 1961 until 2013. The methods used to answer the first objective is by using graph analysis. Whereas, for the second objective is by using Revealed Comparative Advantages (RCA) and Herfindahl Hirschman Index (HHI) method and Self-Sufficiency Ratio( SSR) and Import Dependence Ratio (IDR) method is used to answer the third objective. The result concluded that RCA for Malaysia palm oil industry is more than 1 (RCA= 2.3), which signifies that Malaysia is relatively more specialized in palm oil industry. HHI results calculated that the market share is 4629.67, which means Malaysia palm oil industries at the world market highly concentrated. The average percentage of SSR for Malaysia is more than 100% and the average percentage of IDR is 10%-40%. Its show Malaysia able to develop without strong dependence from other countries that produce palm oil. This clearly pointed out to the fact that Malaysia was strong in exporting of palm oil.